The effect of BIS-guided anaesthesia on the incidence of postoperative nausea and vomiting in children: a prospective randomized double-blind study - Frelich, Michal; Sklienka, Peter; Romanová, Tereza; Němcová, Simona; Bílená, Markéta; Straková, Hana; Lečbychová, Karolína; Jor, Ondřej; Formánek, Martin; Burša, Filip (BMC anesthesiology, 2024)
BACKGROUND: Postoperative nausea and vomiting (PONV) is a significant problem following paediatric surgery, and volatile anaesthetics are an important cause of this phenomenon. BIS-guided anaesthesia, by reducing the consumption of anaesthetics, leads to a decrease in PONV in adult patients. STUDY OBJECTIVE: Evaluate the role of BIS-guided anaesthesia in reducing the incidence of paediatric PONV. DESIGN: Prospective, randomized, double-blind study. SETTING: A single center study in university hospital in Czech republic, from June 2021 to November 2022. PATIENTS: A total of 163 children, aged 3-8 years with ASA I-II who underwent endoscopic adenoidectomy under general anaesthesia were included. INTERVENTIONS: In the intervention group, the depth of anaesthesia was maintained to values between 40 and 60 of BIS. MAIN OUTCOME MEASURE: The primary outcome was the incidence of postoperative nausea and vomiting during 24 h after surgery. RESULTS: The use of BIS-guided anaesthesia led to a significant decrease in the incidence of nausea and vomiting compared to the control group [17% vs. 53%; RR (95%CI) 0.48 (0.27-0.86); p < 0.001and 16% vs. 34%; RR (95%CI) 0.33 (0.20-0.54); p = 0.01, respectively]. CONCLUSIONS: BIS-guided anaesthesia decreases the incidence of postoperative nausea and vomiting in children undergoing adenoidectomy. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT04466579.
Keywords: adenektomie; Female; dítě; předškolní dítě; Postoperative nausea and vomiting; ženské pohlaví; Children; Anesthesia, General; lidé; Adenoidectomy; dvojitá slepá metoda; Postoperative Nausea and Vomiting; Postoperative pain; celková anestezie; Incidence; prospektivní studie; Double-Blind Method; Male; incidence; Prospective Studies; Czech Republic; Child, Preschool; BIS monitoring; Česká republika; Child; mužské pohlaví; pooperační nevolnost a zvracení; Humans